Estrategias de afrontamiento en la frustración en gimnastas de la Federación deportiva de Chimborazo - Sanaylán Martínez, Johanna Gabriela (2017)
The present research project was carried out in the Sports Federation of Chimborazo, its main objective was to analyze coping strategies and frustration in adolescents of artistic gymnastics, the population consisted of 15 adolescents aged between 14 and 17 years, being 66.7% female and 33.3% male. In the research, the descriptive, cross-sectional, and quantitative-type study was used. The data collection techniques and instruments that were used were: Inventory of Assessment and Coping (VAT) of Nora B Leibovich (1992), to evaluate types of cognitive assessment against a stressor and coping strategies. Bar-On (2004), Scale for the evaluation of tolerance to frustration, assesses the perception of children and adolescents about their own capacity for stress management-stress tolerance and impulsive control. After the application of the psychological instruments, the results were analyzed with the Kendall Tau test in the statistical program SPSS version 24.0 IBM. It was possible to determine that adolescents use the type of cognitive coping strategy with greater incidence (66.7%), in addition it could be established that the population mostly identifies the challenge type assessment (66.7%). In the Scale for the evaluation of tolerance to frustration, it can be indicated that the majority of the population has a high level of tolerance to frustration (60%), while a minimum percentage shows a low level of tolerance to frustration ( 6.7%). No direct correlation was found between the study variables, with p = 0.098; however, a correlation was found between frustration and assessment of the situation as challenging with p = 0.009.